Comparable results for the Femoral Neck System and three-screw fixation in femoral neck fracture treatment - Honkanen, Jukka; Forsbacka, Nora; Strengell, Ida; Laaksonen, Inari; Mäkelä, Keijo; Koivisto, Mari; Huovinen, Ville; Ekman, Elina (Ovid, 2025)
Objectives:
To report outcomes of femoral neck fractures (FNFs) treated with Femoral Neck System (FNS) and to compare the risks of later conversion to arthroplasty for FNS and fixation with cannulated screws (CNSs).
Design:
A retrospective study.
Setting:
A single-center study (Turku University Hospital, Finland).
Patients:
Data on 51 patients with FNFs treated with FNS between January 1, 2019, and May 31, 2021, were retrospectively reviewed. In addition, data on 301 patients treated with cannulated screws were collected and analyzed in a previous study.
Intervention:
Patients with FNFs underwent osteosynthesis with FNS.
Main Outcome Measurements:
Patients' preoperative and postoperative radiographs were analyzed and measured to determine preoperative displacement, preoperative posterior tilt, and quality of reduction. Later conversion to arthroplasty and other reoperations were recorded. The risk of later conversion to arthroplasty was compared between the FNS group and CNS group.
Results:
The overall reoperation rate in the FNS group was 20%, and 16% of the patients treated with FNS underwent later conversion to arthroplasty. In the multivariate analysis, age, sex, and fracture displacement were not associated with increased risk of later conversion to arthroplasty. In comparison with fixation with cannulated screws, there was no statistically significant difference in the probability of later conversion to arthroplasty between the groups.
Conclusion:
FNS seems to have a comparable reoperation rate and conversion-to-arthroplasty rate compared with the gold standard treatment.